2022
DOI: 10.1186/s13075-022-02859-x
|View full text |Cite
|
Sign up to set email alerts
|

Senescence in osteoarthritis: from mechanism to potential treatment

Yikai Liu,
Zian Zhang,
Tao Li
et al.

Abstract: Osteoarthritis (OA) is an age-related cartilage degenerative disease, and chondrocyte senescence has been extensively studied in recent years. Increased numbers of senescent chondrocytes are found in OA cartilage. Selective clearance of senescent chondrocytes in a post-traumatic osteoarthritis (PTOA) mouse model ameliorated OA development, while intraarticular injection of senescent cells induced mouse OA. However, the means and extent to which senescence affects OA remain unclear. Here, we review the latent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 168 publications
2
49
0
Order By: Relevance
“…Advanced age is regarded as a separate risk factor for osteoarthritis [ 49 ]. At first, it was found that senescent chondrocytes increased in osteoarthritis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age is regarded as a separate risk factor for osteoarthritis [ 49 ]. At first, it was found that senescent chondrocytes increased in osteoarthritis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of IL-8, VEGF, MCP-1, MCP-2, or MCP-3 has been found in the female genitourinary tract immediately after VD (Wood et al, 2008). These cytokines and chemokines are secreted in inflammatory processes, but they are also part of what is known as SASP or senescence-associated secretory phenotype (Coppe et al, 2010;Lopes-Paciencia et al, 2019). SUI, as other pelvic floor disorders, is not considered an inflammatory disease but rather a multifactorial chronic disorder related to tissue deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Closely associated with cellular senescence is ECM remodeling, a process with consequences on tissue homeostasis. These phenomena feed off each other since some of the molecules that make up the SASP are MMPs or enzymes that degrade the ECM (Coppe et al, 2010;Lopes-Paciencia et al, 2019), and abnormal ECM remodeling is thought to lead to cellular senescence (Blokland et al, 2020). There is also in vivo data on the implication of ECM-degrading enzymes in incontinence, as increased MMP-2 and MMP-9 activity was reported in the vaginal wall after VD (Rahn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis (OA) is the most common joint disease and a degenerative disease. The accumulation of senescent cells in the cartilage is implicated in the development of this pathology [3]. The senescent cells have a senescenceassociated secretory phenotype (SASP) implicated in the intercellular communication between cells [4].…”
Section: Introductionmentioning
confidence: 99%